Pengaruh Manajemen Seni Terhadap Kualitas Pameran di Galeri Salihara Tahun 2013-2018 (Program Studi Pendidikan Seni Rupa FBS UNJ, 2021)
This research goals were to Knowing quality of art and exhibition’s management at Galeri Salihara in 2013-2018, knowing the factors of art management that affects to quality of art exhibition at Galeri Salihara. This research used the methods of qualitative and quantitative (mix-methods) with descriptive approachment. The interviewees were curator and staff of Galeri Salihara. Objects in this research was the management of exhibition and the quality parameters of exhibition. The research setting held at Galeri Salihara which located at Jalan Salihara, number 16, South Jakarta. Data collection techniques that used were observation, interview, document study and assessment questionnaires. While the data analysis techniques that used were descriptive analysis, descriptive statistical analysis and SWOT analysis.The result of this research showed that the exhibition at Galeri Salihara was in the good category. Galeri Salihara has the power to create good concept and curation. However, as a non-profit gallery, Galeri Salihara has obstacles, one of them was funding aspect. This aspect was very important in determining the quality of an exhibition.